3 (y-1/7) — y=4 (2-y) solve for…

Discussion in 'Mathematics' started by Scmqg, Nov 19, 2015.

  1. Scmqg

    Scmqg New Member

    Joined:
    Mar 6, 2015
    Messages:
    0
    Likes Received:
    0
    3 (y-1/7) — y=4 (2-y) solve for y
     
  2. Philipwezt

    Philipwezt New Member

    Joined:
    Feb 16, 2014
    Messages:
    0
    Likes Received:
    0
    3 (y — ¹/₇) — y=4 (2 — y) 3 (y)+3 (⁻¹/₇) — y=4 (2)+4 (-y) 3 y +(⁻³/₇) — y=8+(-4 y) 3 y — ³/₇ — y=8 — 4 y 3 y — y — ³/₇=8 — 4 y 2 y — ³/₇=8 — 4 y +4 y +4 y 6 y — ³/₇=8+³/₇+³/₇ 6 y=8³/₇ 6 6 y=1¹⁷/₄₂
     

Share This Page